NXT2 is a key component of the RNA nuclear export factor complex in the human testis and essential for spermatogenesis - Dicke, Ann-Kristin; Ahmedani, Ammar; Ma, Lin; Herrmann, Leonie; van der Heijden, Godfried W.; Koser, Sophie A.; Krallmann, Claudia; Kalyon, Oguzhan; Xavier, Miguel J.; Veltman, Joris A.; Kliesch, Sabine; Neuhaus, Nina; et al. (NATURE PORTFOLIO, 2025)
In eukaryotes, the nucleocytoplasmic export of bulk poly(A)+-mRNAs through the nuclear pore complex is mediated by the ubiquitously expressed NXT1-NXF1 heterodimer. In humans, NXT1 has an X-chromosomal paralog, NXT2, which exhibits testis-enriched expression, suggesting a role in spermatogenesis. Here, we report the in vivo interaction of NXT2 with crucial components of the nuclear export machinery, including NXF1, the testis-specific NXF1 paralogs NXF2 and NXF3, and nuclear pore complex proteins. Binding to NXF2 and NXF3 is mediated by the NTF2-like domain of NXT2. By identifying infertile men with loss-of-function variants in NXT2 and NXF3, we link the impaired NXT2-NXF activity to disturbed germ cell development. The predominant absence of germ cells in men with NXT2 deficiency indicates its critical function already during fetal or first steps of germ cell development. In contrast, loss of NXF3 affects later stages of spermatogenesis, resulting in quantitatively and qualitatively impaired sperm production.